The Impact of Design Parameters on Energy Demand for Office Renovation - Minyoung Kwon (A+BE: Architecture and the Built Environment)
Chapter 6 showed that the office layout and desk location were the most influential design factors for the thermal and visual comfort of users, and layout and orientation were most influential for psychological comfort in office buildings. Office design parameters were analysed to optimise user satisfaction in relation to indoor environmental and organisational quality in office buildings by showing predictable models. However, the predicted satisfaction models had not been tested in terms of energy performance. Therefore, this chapter evaluates the energy performance of the predicted models by computational assessment.a